2018
DOI: 10.1007/s00213-018-4904-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the abuse liability of three menthol Vuse Solo electronic cigarettes relative to combustible cigarettes and nicotine gum

Abstract: RationaleWe previously reported that following a short-term product use period, use of non-menthol Vuse Solo electronic cigarettes (ECs) resulted in product effect-related subjective responses and nicotine uptake between those of combustible cigarettes (high-abuse liability comparator) and nicotine gum (low-abuse liability comparator); the results were generally closer to those of nicotine gum.ObjectiveUsing a similar design to the previous study, we evaluated the abuse liability of three menthol-flavored Vuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 26 publications
7
44
0
Order By: Relevance
“…‘dizziness’ and ‘nausea’ items comprising the ‘aversion’ subscale of the mCEQ) relative to e‐cigarettes. Similarly, other research has shown that rewarding subjective effects are greater from cigarettes relative to e‐cigarettes following ad‐libitum use and in qualitative interviews . Although nicotine exposure was greater from cigarettes, there was no difference in overall withdrawal symptoms measured by the MNWS.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…‘dizziness’ and ‘nausea’ items comprising the ‘aversion’ subscale of the mCEQ) relative to e‐cigarettes. Similarly, other research has shown that rewarding subjective effects are greater from cigarettes relative to e‐cigarettes following ad‐libitum use and in qualitative interviews . Although nicotine exposure was greater from cigarettes, there was no difference in overall withdrawal symptoms measured by the MNWS.…”
Section: Discussionsupporting
confidence: 49%
“…Similar to de‐nicotinized cigarettes , e‐cigarettes without nicotine can reduce tobacco withdrawal symptoms, but less so than nicotine‐containing e‐cigarettes . However, e‐cigarettes containing nicotine are reported not to reduce withdrawal symptoms as much as cigarettes —perhaps because nicotine delivery is not the only factor in managing cigarette withdrawal symptoms. Differences between e‐cigarette types can affect stimulus characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The pharmacological effects of nicotine are purported to drive these associations, as nicotine has detrimental effects on the neurotransmitters that regulate the sleep–wake cycle (Sabanayagam & Shankar, ; Zhang, Samet, Caffo, & Punjabi, ). Given this proposed mechanism, nicotinized e‐cigarettes, which deliver cigarette‐like levels of nicotine (Goniewicz, Kuma, Gawron, Knysak, & Kosmider, ; Ramôa et al., ; Stiles et al., ; Wagener et al., ), may also be linked to poor sleep health. However, the effects of e‐cigarette use on sleep health remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Drug Alcohol Depend [ 30 ] 60 60 30 (50.0 %) 0 (0.0 %) Stiles, et al, (2018). Psychopharmacology [ 31 ] 220 220 220 220 2019 Hiler, et al, (2019). Experimental and Clinical Psychopharmacology [ 32 ] 256 224 (87.5 %) 128 (50.0 %) 0 (0.0 %) O'Connell, et al, (2019).…”
Section: Resultsmentioning
confidence: 99%